The magnetic structures of rare-earth superlattices - Cowley, R (1998)
Rare-earth superlattices have been grown by a number of groups using molecular beam epitaxy, and the chemical and magnetic structures determined with x-ray and neutron-diffraction techniques. Superlattices of Dy/Y, Ho/Y, Ho/Lu, and Ho/Dy show helical structures in which the magnetic moments are aligned in ferromagnetic sheets within each basal plane, but the orientation of the moments changes from one plane to the next. The magnetic order then propagates coherently from one magnetic layer to the next with a coherence in both the turn angle and chirality of the helix. In contrast there is no coherence in the ordering of the Ho moments from one Ho layer to the next for He/Pr superlattices for which Pr has the dhcp structure and Ho the hcp structure. There is also no coherence in the magnetic structures of He/Sc superlattices for which the lattice mis-match is so large that the Ho and Sc layers have different basal-plane lattice constants. The behaviour is more complex for Ho/Er, Ho/Tm, Er/Y and Er/Lu superlattices which show coherent structures at temperatures where the moments order either in the basal plane or along the c-axis bur when both components order the coherence length decreases as the second component of the moment increases. It is argued that these results are consistent with a model in which if the conduction electrons responsible for the magnetism can propagate through the superlattice a coherent structure is obtained but if they are confined to particular layers when the structure is coherent only over single layers.